PENGARUH PERKEMBANGAN KOGNITIF ANAK TERHADAP PEMBELAJARAN DI SEKOLAH DASAR - Ivon Ayunatasari Maimunah Albay; Dani Rifky Fitra Pradana (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This article aims to explore the influence of children's cognitive development on learning in elementary schools. This article uses the systematic literature review (SLR) research method. This data was obtained from various data sources through search, assessment and analysis from written and trusted sources. The data collection process was carried out by searching for journal literature, articles online using the Google Scholar search engine and Open Knowledge Maps from 2019 to 2024 which had gone through a filtering process from 958 articles to 21 articles. The results of the discussion of this article show that children's cognitive development greatly influences learning in elementary school. Children who have high cognitive abilities will find it easier to receive, capture and understand the material they are studying, and vice versa, children with low cognitive abilities will experience difficulty in receiving, capturing and understanding the material they are studying. A child's cognitive development can be influenced by several factors such as the learning environment, the quality of teaching received by the child, the third factor is the child's diet, and the final factor is the social aspect. Therefore, it is important to collaborate between teachers and parents to understand children's cognitive development stages and develop appropriate learning strategies.